Wave manipulation via delay-engineered periodic potentials - Alberucci, Alessandro; Jisha, Chandroth P.; Monika, Monika; Peschel, Ulf; Nolte, Stefan (Physical Review Research, 2022)
We discuss the semiclassical transverse trapping of waves by means of an inhomogeneous gauge field. In the proposed scheme a temporally periodic perturbation is shifted in time, the imparted delay being dependent on the transverse direction. We show that, due to the Kapitza effect, an effective potential proportional to the square of the transverse derivative of the delay arises. On a more physical ground, the delay induces a transversely varying periodic force acting on the wave, in turn providing a phase delay owing to the local modulation of the kinetic energy. Our results are quite generic and can find application in several fields, ranging from cold atoms to optics: accordingly, an experimental proof-of-principle is provided using an optical setup based upon fiber loops.
CRIS-Team Scopus Importer:2023-04-20